Lepto-philic 2-HDM + singlet scalar portal induced fermionic dark matter - Sukanta Dutta; Ashok Goyal; Manvinder Pal Singh (Journal of High Energy Physics, 2019)
Abstract We explore the possibility that the discrepancy in the observed anomalous magnetic moment of the muon Δa μ and the predicted relic abundance of Dark Matter by Planck data, can be explained in a lepto-philic 2-HDM augmented by a real SM singlet scalar of mass ∼ 10–80 GeV. We constrain the model from the observed Higgs Decay width at LHC, LEP searches for low mass exotic scalars and anomalous magnetic moment of an electron Δa e . This constrained light singlet scalar serves as a portal for the fermionic Dark Matter, which contributes to the required relic density of the universe. A large region of model parameter space is found to be consistent with the present observations from the Direct and Indirect DM detection experiments.